History of Human Schistosomiasis (bilharziasis) in China: From Discovery to Elimination - Zhou, Yibiao; Chen, Yue; Jiang, Qingwu (Acta parasitologica, 2021)
Purpose For the evolution of schistosomiasis in China, a systematic review was provided about the history of the disease and its public health impacts. We aimed to depict the journey from disease discovery to elimination and the experience and lessons learned during the process. Methods We systematically reviewed the Chinese history of schistosomiasis and its public health impacts and collected data on the disease by searching relevant books and articles. Results An important milestone for the disease discovery is that Schistosoma japonicum eggs were identified in the two Chinese corpses dating back to around 2180 years ago. The earliest Chinese ancient book documented symptoms resembling schistosomiasis that could date back to about 4700 years ago. The first nationwide survey on the disease in the mid-1950s revealed that schistosomiasis was endemic in 433 counties or cities of 12 provinces and affected about 11.6 million people in China. The Chinese government has provided continuous investment in schistosoiasis control, and the national multifaceted, integrated control programs have been uninterruptedly implemented since 1955. Schistosomiasis control in China can be divided into six stages, and various schistosomiasis control strategies have been developed and adjusted. The number of schistosomiasis cases decreased from 11.6 million in 1950s to 38,000 in 2017 and the number of acute cases decreased from 13,191 in 1989 to only 1 in 2017. Conclusions Schistosomiasis transmission has been under control in all parts of China since 2017. An elimination of schistosomiasis can be achieved in the foreseeable future in China.